(untitled) (Prashasan: The Nepalese Journal of Public Administration, 2023)
The research paper discusses corruption in Nepal’s public sector, a significant challenge in the development agenda. The main objective of this study is to find the causes and consequences of corruption in the public sector. This study used primary and secondary data to determine the causes and consequences of corruption in Nepal. The results found that the political, court, and administration sectors are the most corruption-prone zones, losing the government’s credibility. The leading causes of corruption are non-compliance with existing rules and regulations, lack of political commitment, transparency, accountability, consistency, and institutional weaknesses. Corruption reduces competitiveness and increases the cost of living, becoming a significant obstacle to economic growth, social development, and political stability. The government has taken various measures to combat corruption, including establishing anti-corruption bodies and laws. However, these measures have yet to be effective in curbing corruption, and there is a need for more significant reforms. The political leader, bureaucrats, civil society, and media should take responsibility for controlling corruption in the public sector of Nepal.